2016
DOI: 10.1038/srep23472
|View full text |Cite|
|
Sign up to set email alerts
|

Small molecule-mediated up-regulation of microRNA targeting a key cell death modulator BNIP3 improves cardiac function following ischemic injury

Abstract: Genetic ablation of BCL2/adenovirus E1B 19 kDa protein-interacting protein 3 (BNIP3), an essential regulator of cardiac cell death, is an effective way to prevent cardiac cell death triggered by pathologic conditions. However, currently there exists no known means, such as inhibitors, to down-regulate BNIP3 in mature heart. Here, we report that a small molecule inducer of microRNA-182 (miR-182) suppressed ischemia/reperfusion (I/R)-induced cardiac cell death by down-regulating BNIP3. We first selected miR-182 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 44 publications
(46 reference statements)
0
17
0
Order By: Relevance
“…35) MiR-182 prevents ischemiainduced cardiac cell death by suppressing BNIP3 expression. 36) The above mentioned findings suggest that downregulating the expression of pro-apoptotic BNIP3 is beneficial for cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…35) MiR-182 prevents ischemiainduced cardiac cell death by suppressing BNIP3 expression. 36) The above mentioned findings suggest that downregulating the expression of pro-apoptotic BNIP3 is beneficial for cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…The Bcl-2 interacting protein 3 (BNIP3) 3′-untranslated region (UTR) containing complementary sequences or the mutated sequence for the seed sequence of miR-182 was amplified by PCR as described previously (25), and cloned into the firefly luciferase expressing vector, pGL3 (Promega Corporation); the vectors were denoted as wild-type (wt) pGL3-BNIP3-3′-UTR and mutant (mut) BNIP3-3′-UTR, respectively. For the luciferase reporter assay, 293T cells (American Type Culture Collection) were seeded into a 24-well plate (5.0×10 5 /well) and transfected with the wt or mut reporter vector, together with miR-182 mimics or miR-182 inhibitor using Lipofectamine 2000.…”
Section: Methodsmentioning
confidence: 99%
“…16 The disruption of BNIP3 inhibits apoptosis, is crucial for ischemic cardiomyocytes, and is important for cardiac cell survival 16, 17, 18, 19, 20. We also reported that downregulating BNIP3 is an effective means to prevent cardiac cell death 21 . Nevertheless, inhibition of necroptosis or apoptosis remains limited as a therapeutic treatment in heart disease.…”
Section: Introductionmentioning
confidence: 98%